2020
DOI: 10.1111/1556-4029.14303
|View full text |Cite
|
Sign up to set email alerts
|

Cold Case Experiment Demonstrates the Potential Utility of Aquatic Microbial Community Assembly in Estimating a Postmortem Submersion Interval

Abstract: Microbial community assembly (MCA) of both human and nonhuman animal carcasses provides indicators useful for estimating the postmortem interval (PMI) in terrestrial settings. However, there are fewer studies estimating postmortem submersion intervals (PMSIs) in aquatic habitats. No aquatic studies to date assessed MCA in the context of a death investigation, with all previous studies focusing on important basic ecological questions. Within the context of a cold case investigation, we performed an experiment u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(53 citation statements)
references
References 50 publications
3
50
0
Order By: Relevance
“…These findings corroborate those by Cartozzo et al (16) but also augment them since we examined entire carcasses over a short period and where they examined two types of bone over a longer period. Our findings suggest that habitat‐specific taxa, i.e., along a fresh to brackish water continuum commonly observed in a tidal‐influenced river system (56) as well as how they change in relative abundance during decomposition (e.g., describing habitat‐specific MCA) can be utilized to predict a PMSI through the use of machine learning algorithms as demonstrated by Kaszubinski et al (15) and Cartozzo et al (16). The increased use of machine learning modeling like we have done here illustrates how powerful this tool can be for elucidating complex patterns in microbial community datasets and underscores how a diverse microbial community, as well as the reproducibility of microbial community succession, can be used to predict PMI in terrestrial environments and PMSI in aquatic ecosystems (57).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…These findings corroborate those by Cartozzo et al (16) but also augment them since we examined entire carcasses over a short period and where they examined two types of bone over a longer period. Our findings suggest that habitat‐specific taxa, i.e., along a fresh to brackish water continuum commonly observed in a tidal‐influenced river system (56) as well as how they change in relative abundance during decomposition (e.g., describing habitat‐specific MCA) can be utilized to predict a PMSI through the use of machine learning algorithms as demonstrated by Kaszubinski et al (15) and Cartozzo et al (16). The increased use of machine learning modeling like we have done here illustrates how powerful this tool can be for elucidating complex patterns in microbial community datasets and underscores how a diverse microbial community, as well as the reproducibility of microbial community succession, can be used to predict PMI in terrestrial environments and PMSI in aquatic ecosystems (57).…”
Section: Discussionmentioning
confidence: 67%
“…Compared to studies conducted in terrestrial habitats, only a few have investigated microbial community succession using high throughput sequencing on carcasses in aquatic habitats (13)(14)(15)17), and none from intertidal or estuarine ecosystems. The few aquatic studies using carcass microbiome assembly for predicting PMSI have been in freshwater small streams (13,14) and an isolated freshwater pond (15,16). Thus, there is limited knowledge on how specific, and important, abiotic factors such as salinity have on the endogenous microbial communities representing a certain type of aquatic habitat (e.g., freshwater stream compared to a pond or the estuary of a river).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, this initial work with a limited PLOS ONE sample set demonstrated that both community structure and some individual bacterial taxa could be used to classify sample time point categories (e.g., PMI) with reasonable accuracy; however, there was not sufficient statistical power to perform regression models to better represent a continuous timeline. While we were limited to modeling individual time points and not along a continuum, the descriptive characterizations (e.g., community diversity and taxa relative composition) did show qualitative successional changes over time that could be potentially useful in identifying individual taxa as important to indicators of large differences in time since burial, much like that done recently in an aquatic habitat [75]. Such information has potential forensic utility especially in cases when other forms of evidence (e.g., insects) are not available.…”
Section: Microbiomementioning
confidence: 99%